The determinants and effects of FDI flows from the EU-15 to UE-12: The case of Poland and Hungary - Wojciechowski, Liwiusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The purpose of this article is to test the hypothesis stating that the gravity model of international trade explains the flow of the FDI from the old EU 15 to the new EU 12 member states satisfactorily. It has been decided to explain how the augmentation of the classic gravity model of international trade allows for the identification of “push” and “pull” FDI factors. The empirical analysis has been conducted with the use of panel data approach using Hausman-Taylor estimator. General results allows for the verification of the main hypothesis positively, however some anomalies have been observed. While investment decisions concerning the selection of the target country are determined by the size of the market measured by GDP per capita, the geographical distance is still a destimulant of FDI despite the globalisation processes. The membership in the EU, EMU, taxation differences, historical background seem to be important factors in the context of investment flows direction. It has been also pointed out that Poland was a leader on the background of the FDI inflow from the EU 15. This study shows that the inflow of FDI has generally a positive effect on economic growth in many areas. In the light of empirical research, the impact of FDI on the economy seems to be positive, though in varying degrees when analyzing different countries. This is conclusive with the claim that the effects of FDI inflows on the economy of the host country depend on the initial conditions in these countries. This also suggests that individual countries should create a specific mechanism for attracting investments that should base on strengthening the existing advantages.